Rutinitas Manaqib Nurul Burhan dalam Meningkatkan Ketakwaan Masyarakat di Dukuh Sekuwung Sukorejo Ponorogo - Taufiqurrohman Taufiqurrohman; Khusnul Khotimah (Social Science Academic, 2025)
Islamic traditions are very integrated in the activities of the Islamic community in Indonesia, which are carried out by all levels of society, for example the religious organization Nahdlatul Ulama (NU) which takes the form of religious rituals that have been taught by Ulama such as the reading of Nurul Burhan's manaqib. For example, the Manaqib Nurul Nurhan congregation in Dukuh Sekuwung carries out the Manaqib Nurul Burhan routine every evening on the 11th of the Hijriyah month. This activity is carried out in the Madrasah Diniyah Mamba’ul Ulum hall for about 1 year. The aim is to deepen the feeling of love for Allah through appreciation of the life stories of Suffi experts. This research uses a qualitative descriptive method using field-based data collection techniques for observation and interviews conducted with manaqib leaders and residents who took part in the activity. The problem is how the routine of Nurul Burhan's manaqib can increase the devotion of the residents of Dukuh Sekuwung. The problem is that society's ignorance or shallow understanding of the historical context and teachings under the figures in Manaqib causes deviations in the application of teachings. The results of this research are that Manaqib Nurul Burhan can be an effective spiritual means for deepening love and devotion to Allah SWT, as long as it is carried out with sincere intentions and correct understanding. ‎